Comparative Study on the Catalytic Performance of a 13X Zeolite and its Dealuminated Derivative for Biodiesel Production - Balqees A. Alshahidy; Ammar S. Abbas (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Natural kaolin clay was used to successfully prepare 13X zeolite catalysts, which were modified by dealumination with citric acid. Acid leaching eliminates impurities and aluminum, and improves the Si/Al ratio of the zeolite framework. The X-ray diffraction (XRD) patterns of both the original and modified 13X zeolites were the same, indicating that the crystalline frameworks were not destroyed during the dealumination process. X-ray fluorescence data of the dealuminated 13X zeolite showed an improved Si/Al ratio. Also, Atomic Force Microscopy (AFM) was used for the characterization of the catalysts. The catalytic performance of the original and modified catalysts was tested in the esterification reaction of oleic acid in a batch reactor. A higher conversion of oleic acid was obtained using the modified 13X zeolite. The resulting experimental data from the esterification reactions were fitted to the heterogeneous Langmuir-Hinshelwood-Hougen-Watson (LHHW) kinetic model to determine the rates of reaction. The results of the reaction kinetics showed an increase in the rate of reaction velocity and a distinct decrease in the activation energy when using the modified zeolite, indicating that employing the modified catalyst will give a higher conversion over a shorter time through a reaction with less sensitivity to temperature. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).